Composition, member, and protective equipment

By using resin particles and ionic liquid in the diluent olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-based olefin oil-

JP7658556B2Active Publication Date: 2025-04-08NAT INST FOR MATERIALS SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021029835
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-26
Publication Date
2025-04-08
Estimated Expiration
2041-02-26

AI Technical Summary

Technical Problem

The diluent olefin oil-based gluten oil-based gluten oil composition in the prior art has insufficient stability, especially in applications with high requirements for fire stability, which poses safety risks.

Method used

By using resin particles and ionic liquid in the composition, the volume fraction of the resin particles is between 41.0% and 80.0% and the maximum absorption wavelength of the ionic liquid is between 510 and 570 nanometers, forming a swelling agent composition that does not contain flammable liquids.

Benefits of technology

The high fire stability and excellent swelling properties of the composition are achieved, while avoiding the use of flammable liquids and improving safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007658556000011
    Figure 0007658556000011
  • Figure 0007658556000012
    Figure 0007658556000012
  • Figure 0007658556000013
    Figure 0007658556000013
Patent Text Reader

Abstract

To provide a composition having excellent dilatancy without containing a combustible liquid.SOLUTION: A composition contains resin particles and ionic liquid. In the composition, the content of the resin particles is 41.0-80.0 vol.%. A solution made by dissolving (Acethylacetonate)(N, N, N', N'-tetramethylethylenediamine)copper(II)tetraphenylborate in the ionic liquid has a maximum absorption wavelength λCu of 510-570 nm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composition, a member, and a protective device. [Background technology]

[0002] Compositions that exhibit dilatancy are known. As one such composition, Patent Document 1 describes a "dilatancy composition containing (A) 100 parts by mass of a styrene-based elastomer, (B) 250 to 350 parts by mass of a softener, and (C) 250 to 350 parts by mass of an alicyclic saturated hydrocarbon resin having a softening point of 135° C. or higher." [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2018-80236 A Summary of the Invention [Problem to be solved by the invention]

[0004] According to the study by the present inventors, the composition described in Patent Document 1 contains a flammable oil such as paraffin oil as a softener, and there is room for improvement in terms of stability. Therefore, an object of the present invention is to provide a composition that has excellent dilatancy even without containing a flammable liquid. [Means for solving the problem]

[0005] As a result of extensive investigations aimed at achieving the above object, the present inventors have found that the above object can be achieved by the following configuration.

[0006] [1] A composition comprising resin particles and an ionic liquid, wherein the content of the resin particles in the composition is 41.0 to 80.0 volume %, and the maximum absorption wavelength λCu of a solution obtained by dissolving (Acethylacetonate)(N,N,N',N'-tetramethylethylenediamine)copper(II)tetraphenylborate in the ionic liquid is 510 to 570 nm. [2] The composition according to [1], wherein the resin particles have an average particle size of 0.1 to 100 μm. [3] The composition according to [1] or [2], wherein the resin particles contain a crosslinked resin. [4] The composition according to any one of [1] to [3], wherein the resin particles are acrylic resin particles. [5] The composition according to any one of [1] to [4], wherein the resin particles have an average particle size of 1 to 20 μm. [6] The composition according to any one of [1] to [5], having a dilatancy coefficient of 3.00 or more. [7] A member having two opposing shell layers and a composition layer containing the composition according to any one of [1] to [6], disposed between the shell layers. [8] Protective equipment having the components described in [7]. Effect of the Invention

[0007] According to the present invention, a composition having excellent dilatancy even without containing a flammable liquid can be provided. Also, according to the present invention, a member and a protective device can be provided. [Brief description of the drawings]

[0008] [Figure 1] 1 is a schematic cross-sectional view of a member containing a composition of the present invention. [Diagram 2] 1 is an embodiment of a protective device including a member of the present invention. [Diagram 3] 1 is a glove according to another embodiment of the protective equipment of the present invention. [Figure 4]1 is a headgear according to another embodiment of the protective equipment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention will be described in detail below. The following description of the components may be based on a representative embodiment of the present invention, but the present invention is not limited to such an embodiment. In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits.

[0010] (Definition of terms) In this specification, the "dilatancy coefficient" refers to the ratio of the viscosity at a shear stress of 1,000 Pa to the viscosity at a shear stress of 10 Pa when shear rheology measurements are performed at 20°C using a rotational viscometer. That is, the dilatancy coefficient is a value defined by the formula: (dilatancy coefficient)=(viscosity at shear stress of 1000 Pa) / (viscosity at shear stress of 10 Pa). The shear rheology measurement is carried out according to the method described in the Examples, and the dilatancy coefficient is rounded off to two decimal places and calculated as a number to two decimal places. However, if the dilatancy coefficient is less than 0.01, the above rule is not applied and it is to be expressed to three significant digits.

[0011] In this specification, the state in which the composition "has dilatancy" means a state in which the above-mentioned dilatancy coefficient exceeds 1.50, preferably 3.00 or more, more preferably 5.00 or more, even more preferably 7.00 or more, and particularly preferably 9.00 or more. There is no particular upper limit, but generally, it is preferably 500.00 or less.

[0012] [Composition] The composition according to an embodiment of the present invention contains resin particles and a specified ionic liquid, and the content of the resin particles in the composition (in other words, when the total volume of the composition is 100 volume %) is 41.0 to 80.0 volume %. The composition contains an ionic liquid as a main liquid component, and therefore has excellent stability and excellent flame retardancy. The composition also has excellent dilatancy.

[0013] The mechanism by which the above composition exhibits excellent dilatancy is not entirely clear, but the present inventors speculate as follows: Note that the following mechanism is merely speculation, and even if the problem is solved by a mechanism other than the following mechanism, it is still within the scope of the present invention.

[0014] This composition contains 41.0 to 80.0 volume % of resin particles in an ionic liquid. Therefore, in the composition, the particles are likely to come into contact with each other and are likely to be in a so-called "dense" state. In general, when resin particles are in such a "dense" state in a liquid, the resin particles are characterized by being likely to form aggregates.

[0015] It is believed that in order for a particle dispersion to exhibit dilatancy, the particles approach each other and become dense when subjected to a large stress, and when the stress is removed or reduced, the particles need to disperse again.

[0016] The present inventors have been studying methods for obtaining a reversibly stable dispersion form in an ionic liquid without forming aggregates of resin particles that have become dense. As a result, they have found that the above is possible even when the resin particles are in a dense state by making the surfaces of the resin particles lubricated with the ionic liquid, and that to achieve this, it is necessary to adjust the affinity between the ionic liquid and the resin particles to an appropriate range.

[0017] It has been experimentally demonstrated that the affinity (e.g., solubility) between an ionic liquid and a target substance is greatly affected by the type of anion in the ionic liquid. However, when focusing on the chemical structure of the anion, it was not necessarily clear what specific factors influenced the affinity with the target substance.

[0018] Under such circumstances, the inventors have focused on the fact that the chemical structure of the anion is related to the electron pair donating property of the ionic liquid, and have investigated the relationship between the anion chemical structure and the electron pair donating property of the ionic liquid. Cu We have continued to conduct experiments and studies to investigate the relationship between the affinity between the target object and the target object. As a result, surprisingly, λ Cu The present invention was completed based on the findings that when the wavelength is in the range of 510 to 570 nm, the resin particles that have become dense are unlikely to form aggregates, and as a result, a composition having excellent dilatancy can be obtained. Each component contained in the composition will be described in detail below.

[0019] <Resin particles> The composition contains resin particles. The content of the resin particles in the composition is 41.0 to 80.0% by volume. If the content of the resin particles is less than 41.0% by volume, the resin particles in the composition become more "sparse" and are less likely to come into contact with each other, resulting in no dilatancy. On the other hand, if the content of the resin particles exceeds 80.0% by volume, the composition tends to become non-uniform, and therefore dilatancy cannot be obtained.

[0020] The content of the resin particles is more preferably 45.0% by volume or more, even more preferably 47.0% by volume or more, particularly preferably 50.0% by volume or more, and most preferably 55.0% by volume or more, in order to obtain a composition having a more excellent effect of the present invention. The upper limit is not particularly limited, but is preferably 75.0% by volume or less, and more preferably 70.0% by volume or less. The resin particles may be used alone or in combination of two or more kinds. When two or more kinds of resin particles are used in combination, the total content thereof is preferably within the above numerical range.

[0021] In this specification, the content of resin particles in a composition means a value determined by the following method (all values ​​are at 25° C.). (Resin particle content: volume %) = (Resin particle content: g) / True specific gravity of resin particles / (Ionic liquid content: mL) × 100

[0022] The average particle size of the resin particles is not particularly limited, but is preferably 0.1 to 100 μm, and more preferably 1 to 20 μm, in that a composition having a more excellent effect of the present invention can be easily obtained.

[0023] The resin particles are preferably insoluble or poorly soluble in the ionic liquid. If the resin swells in the ionic liquid but does not dissolve or diffuse monomolecularly, a composition having excellent dilatancy can be obtained. In this respect, the primary structure of the resin is not particularly limited. Specific examples of the resin are not particularly limited, but include polyolefin resin, polyurethane resin, polyester resin, epoxy resin, melamine resin, polystyrene resin, acrylic resin, polyamide resin, polyether resin, and silicone resin. In particular, from the viewpoint of swelling in the ionic liquid but not dissolving or diffusing monomolecularly and being stable, the resin particles preferably contain a crosslinked (chemically crosslinked) resin, and crosslinked acrylic resins and crosslinked polyether resins (which may contain aromatic groups) are preferred.

[0024] Specific examples of resin particles include cross-linked polystyrene resin particles such as the "SX Series" manufactured by Soken Chemical Industry Co., Ltd. and the "Technopolymer SBX" series manufactured by Sekisui Chemical Co., Ltd.; cross-linked acrylic resin particles such as the "MR Series," "MX Series," and "SX Series" manufactured by Soken Chemical Industry Co., Ltd., and the "Technopolymer MBX" series and "BMX Series" manufactured by Sekisui Chemical Co., Ltd.; and cross-linked silicone resin particles such as the "Tospearl" series manufactured by Montiv Performance Materials and the "KMP Series" manufactured by Shin-Etsu Chemical Co., Ltd.

[0025] <Ionic liquid> The composition contains an ionic liquid. The content of the ionic liquid in the composition is not particularly limited, but when the total volume of the composition is taken as 100 volume%, it is preferably 10.0 volume% or more, more preferably 15.0 volume% or more, even more preferably 20.0 volume% or more, particularly preferably 25.0 volume% or more, and most preferably 30.0 volume% or more. The content of the ionic liquid in the composition is 59.0 volume% or less, more preferably 55.0 volume% or less, and even more preferably 45.0 volume% or less.

[0026] The ionic liquid may be used alone or in combination of two or more. When two or more ionic liquids are used in combination, the total content thereof is preferably within the above numerical range. In this specification, the ionic liquid refers to a non-volatile salt having a melting point of 25° C. or lower under atmospheric pressure.

[0027] The ionic liquid has a maximum absorption wavelength λ of a solution obtained by dissolving (acetylacetonate)(N,N,N',N'-tetramethylethylenediamine)copper(II) tetraphenylborate [(acetylacetonato)(N,N,N',N'-tetramethylethylenediamine)copper(II) tetraphenylborate, a compound represented by the following formula]. Cu However, it is 510 to 570 nm. λ Cu If the wavelength exceeds 570 nm, dilatancy cannot be obtained. Cu is generally 510 nm or more, and within this range, a composition having excellent dilatancy can be obtained.

[0028] [ka]

[0029] λ Cu The values ​​are measured by the following method. First, a measurement solution is prepared by dissolving (acethylacetonate)(N,N,N',N'-tetramethylethylenediamine)copper(II)tetraphenylborate (hereinafter simply referred to as "dye") in the ionic liquid to be evaluated.

[0030] The ionic liquid to be measured is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonate)imide. First, 10 mg of dye is added to 1 mL of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonate)imide, and the mixture is stirred at 300 rpm for 20 minutes using a stirrer to obtain a stock solution for measurement. Next, this stock solution is diluted 100 times to obtain a diluted solution. Next, 20 μL of the diluted solution is added to 1 mL of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonate)imide to obtain a measurement solution.

[0031] The absorbance is measured at room temperature (25°C) using an ultraviolet-visible spectrophotometer (Shimadzu Corporation, product name "UV-2600"). Specifically, the wavelength range of 300 to 600 nm (optical path length 10 mm) is measured. From the obtained absorption spectrum, the maximum absorption wavelength λ Cu In this case, the wavelength is λ Cu The concentration of the measurement solution is adjusted so that the absorbance at

[0032] An example of such an ionic liquid is an ionic liquid represented by the following formula:

[0033] [ka]

[0034] The cations constituting the ionic liquid are, as a whole, λ Cuis within a predetermined range, there is no particular limitation, and known cations can be used. Among them, at least one selected from the group consisting of organic cations and metal complex cations is preferred, and it is preferable that the composition contains an organic cation, and it is preferable that the composition consists of an organic cation, in order to obtain a composition having a better effect of the present invention. In this specification, the organic cation means a cation that does not contain a metal atom and has at least one carbon atom.

[0035] The organic cation is not particularly limited, but examples thereof include onium ions. More specifically, ammonium ions (e.g., R A 4N + ), iminium ions (e.g., R B 2C=N + R 1 2), sulfonium ions (e.g., R A 3S + ), oxonium ions (e.g., R A 2O + ), phosphonium ion (representative structure: R A 4P + ), iodonium ions (e.g., R A 2I + In each of the above formulas, R A R represents a substituent such as an alkyl group, an aryl group, or a heterocyclic group. B represents a hydrogen atom or a monovalent substituent. 1 , multiple R in molecule B , or R in the molecule A and RB may be bonded to each other to form a ring. A , or two R B together form a double bond group (e.g., =O, =S, =NR B ) may be formed.

[0036] Other forms of cations include ammonium ions, pyrrolidinium ions, pyridinium ions, piperidinium ions, oxazolium ions, oxazolinium ions, imidazolium ions, thiazolium ions, and phosphonium ions, as well as derivatives thereof. Of these, ammonium ions, imidazolium ions, pyridinium ions, pyrrolidinium ions, and derivatives thereof are preferred.

[0037] Ammonium ion An example of the ammonium ion is a cation represented by the following formula 1.

[0038] [ka]

[0039] In formula 1, R 1 Each independently represents a hydrogen atom or a monovalent substituent, and a plurality of R 1 may be the same or different. 1 The monovalent substituent is not particularly limited, and examples thereof include substituted or unsubstituted hydrocarbon groups having 1 to 15 carbon atoms which may have a heteroatom.

[0040] Among them, there are four R 1 At least one of them is preferably a methyl group, and at least one of them is preferably a hydrocarbon group having 2 to 10 carbon atoms which may have an oxygen atom.

[0041] Pyrrolidinium ion An example of the pyrrolidinium ion is a cation represented by the following formula 2. [ka]

[0042] In formula 2, R 2 Each independently represents a hydrogen atom or a monovalent substituent, and a plurality of R2 may be the same or different. 2 The monovalent substituent is not particularly limited, and examples thereof include substituted or unsubstituted hydrocarbon groups having 1 to 15 carbon atoms which may have a heteroatom.

[0043] Among them, there are two R 2 It is preferable that one of them is a methyl group, and the other is a hydrocarbon group having 2 to 10 carbon atoms which may have a heteroatom.

[0044] Piperidinium ion An example of the piperidinium ion is a cation represented by the following formula 3. [ka]

[0045] In formula 3, R 3 Each independently represents a hydrogen atom or a monovalent substituent, and a plurality of R 3 may be the same or different. 3 The monovalent substituent is not particularly limited, and examples thereof include substituted or unsubstituted hydrocarbon groups having 1 to 15 carbon atoms which may have a heteroatom.

[0046] Pyridinium ion An example of the pyridinium ion is a cation represented by the following formula 4. [ka]

[0047] In formula 4, R 4 Each independently represents a hydrogen atom or a monovalent substituent, and a plurality of R 4 may be the same or different. 4The monovalent substituent is not particularly limited, and examples thereof include substituted or unsubstituted hydrocarbon groups having 1 to 15 carbon atoms which may have a heteroatom, and more preferably a hydrocarbon group having 2 to 10 carbon atoms which may have an oxygen atom.

[0048] Imidazolium ion An example of the imidazolium ion is a cation represented by the following formula 5. [ka]

[0049] In formula 5, R 51~53 R each independently represents a hydrogen atom or a monovalent substituent, and may be the same or different. 51~53 The monovalent substituent is not particularly limited, and examples thereof include substituted or unsubstituted hydrocarbon groups having 1 to 15 carbon atoms which may have a heteroatom. Among these, R 52 is preferably a hydrogen atom, and R 51 , or R 53 It is more preferable that one of them is a methyl group and the other is a hydrocarbon group having 2 to 10 carbon atoms which may contain an oxygen atom.

[0050] The phosphonium ion may, for example, be a cation represented by the following formula 6: [ka]

[0051] In formula 6, R 6 Each independently represents a hydrogen atom or a monovalent substituent, and a plurality of R 6 may be the same or different. 6 The monovalent substituent is not particularly limited, and examples thereof include substituted or unsubstituted hydrocarbon groups having 1 to 15 carbon atoms which may have a heteroatom. R 6The hydrocarbon group is not particularly limited, but a linear alkyl group having 1 to 15 carbon atoms is preferred.

[0052] The anions constituting the ionic liquid are, as a whole, λ Cu is within the specified range, and any known anion can be used. Examples of anions include Cl. - , Br - , AlCl4 - , Al2Cl7 - , NO3 - , BF4 - , PF6 - , CH3COO - , CF3COO - , CF3SO3 - , (CF3SO2)2N - , (C2F5SO2)2N - , AsF6 - , SbF6 - , F(HF) n - , C4F9SO3 - , (C2F5SO2)2N - , C3F7COO - , CH3SO4 - , C2H5SO4 - , HOSO4 - , H3CO3 - , CH3CH(OH)COO - , and SCN - (CF3SO2)2N - , BF4 - , PF6 - , and (C2F5SO2)2N - At least one anion selected from the group consisting of:

[0053] (Manufacturing method) The method for producing the composition is not particularly limited, and the above-mentioned components may be mixed and stirred. The stirring method is not particularly limited, and any known method may be used. The stirring can be carried out, for example, in a temperature range of 10 to 100° C. using a device such as a planetary centrifugal mixer.

[0054] (Application) The composition has excellent dilatancy. The composition functions as an energy absorbing material, and can therefore be used as protective equipment such as bulletproof clothing, bulletproof vests, bulletproof jackets, clothing, martial arts equipment, helmets, shin guards, elbow pads, gloves, ski boots, snowboard boots, motorcycle equipment, skates (e.g., hockey skates, figure skates, racing skates, etc.), athletic shoes, and orthopedic casts and braces, or as a component of such protective equipment (e.g., pads).

[0055] [Part] 1 is a schematic cross-sectional view of a member containing the present composition. Member 10 is an energy absorbing member that is fixed onto an object to be protected (e.g., a body part of a human or animal), and is typically used as a pad constituting a protective gear.

[0056] The member 10 has, from the side to be protected, a shell layer 11, a composition layer 12, and an outer shell layer 13.

[0057] The outer shell layer 13 and the shell layer 11 function as a container that covers the composition layer 12. The materials of the outer shell layer 13 and the shell layer 11 are not particularly limited, and may be relatively hard materials made of high strength materials such as glass, graphite, para-aramid (e.g., product name "Kevlar"), and ultra-high molecular weight polyolefin (e.g., product name "Spectra"), etc.

[0058] High-strength materials may shatter when subjected to a large stress. However, since the present member has the composition layer 12 containing the composition already described (preferably consisting of the composition) as an intermediate layer, even if the outer shell layer 13 and the shell layer 11 are made of the above-mentioned high-strength material, the composition layer 12 absorbs the impact and prevents the outer shell layer 13 and the shell layer 11 from shattering, thereby preventing the wearer from being injured.

[0059] On the other hand, when the outer shell layer 13 and the shell layer 11 are made of a flexible material, the entire member 10 can deform in accordance with the deformation of the composition layer 12 . In particular, when used as protective equipment for humans or animals, it is capable of deforming to follow the movements of the object to be protected, and when a large external force is applied, the impact is unlikely to be transmitted to the object to be protected.

[0060] Materials that can be used for the outer shell layer 13 and shell layer 11 having such flexibility include polyolefin, polyamide, polystyrene, ethylene-vinyl acetate, nylon, polyester, polyethylene, polytetrafluoroethylene, silicone, vinyl resin, polyurethane, polyvinyl chloride, latex rubber, and polyvinylidene fluoride.

[0061] The thickness of each of the shell layer 11, the composition layer 12, and the outer shell layer 13 is not particularly limited and may be appropriately selected depending on the application. For example, when used to protect the human or animal body, a thickness of 0.1 mm to 0.3 m is generally preferred. Although the member 10 has a flat plate shape, the shape of the member of the present invention is not limited to the above, and may be a three-dimensional shape having a curved surface. The member may also have a layer other than those described above. Examples of such layers include an adhesive layer provided on the surface of the shell layer 11 opposite to the composition layer 12. When the member has an adhesive layer, the member can be easily fixed to the object to be protected.

[0062] [Protective equipment] 2 shows one embodiment of a protective gear including the above-mentioned members. The protective gear 20 is a shirt, and is designed to be worn alone or under or over another garment. The protective gear 20 is composed of a main body 21 and a plurality of pads (made of the above-mentioned members and having a flexible shell) arranged on the main body 21, and each pad is arranged to protect soft tissues, vital organs, etc.

[0063] Specifically, it has shoulder pads 22 to protect both shoulders, arm pads 23 to protect the upper arms, a chest pad 24 to protect the front of the body, and elbow pads 25 to protect the elbows, and a back pad (not shown) to protect the back is provided on the back. These pads are made of the materials already described, and due to the dilatancy of the composition layer, the wearer of the protective equipment 20 is protected from impacts while the wearer's movements are not hindered.

[0064] It should be noted that the protective equipment 20 is in the form of a shirt, but the form of the protective equipment of the present invention is not limited to the above. Fig. 3 shows gloves according to another embodiment of the protective equipment of the present invention. The glove 30 has a main body 31 and a pad 32 (made of the above-mentioned material and having a flexible shell) arranged on the main body, and the pad 32 is arranged at a position where it can protect the metacarpophalangeal joint. The pad 32 can follow the movement of the metacarpophalangeal joint and does not interfere with the movement of the wearer's fingers. On the other hand, when a strong external impact is received, the pad 32 protects the joint.

[0065] 4 shows a headgear according to another embodiment of the protective equipment of the present invention. The headgear 40 is composed of a main body 41 and a plurality of pads 42 (made of the above-mentioned material and having a flexible shell) arranged on the main body 41. In this embodiment, the pads 42 are arranged on the entire outside of the main body 41, and protect the entire head, which is easily damaged in sports such as combat sports, and also fit the shape of the wearer's head due to the dilatancy of the composition layer, and do not hinder the wearer's vigorous movements.

[0066] The protective gear of the present invention is not limited to the above embodiment and may be applied to other articles, such as vehicle seat covers, seat cover linings, carpets, seat belt covers, trunk floor covers, etc. It may also be included as a part of airbags, steering wheels, cargo barriers, bumpers, hoods, window frames, etc. EXAMPLES

[0067] The present invention will be described below with reference to examples, but the present invention is not limited to these.

[0068] [Preparation of Composition] The resin particles (Sekisui Chemical "Techpolymer" MBX-8, average particle size 8 μm, cross-linked polymethylmethacrylate, true specific gravity 1.20) listed in Table 1 were weighed with an electronic balance. The ionic liquid was weighed with a pipette with a capillary piston for weighing high-viscosity liquids (product name "Microman E", manufactured by M&S Instruments Inc.). The weighed materials were introduced into a transparent centrifuge tube made of TPX (product name "Hitech Tube Crystal", manufactured by Hitech Corporation), and then stirred for 6 minutes using a planetary centrifugal mixer (product name "AWADA TURN AW108", manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) to obtain each composition. Table 1 shows the composition of each composition. The content (volume %) of the resin particles in Table 1 was calculated from the true specific gravity of the resin particles.

[0069] [Shear rheology measurements] The shear rheology of the prepared composition was measured using a modular compact rheometer MCR 102 (Anton Paar) equipped with a 25 mm diameter parallel plate at a measurement temperature of 20°C.

[0070] First, the apparatus was started up, and after performing the apparatus calibration before the measurement, the measurement sample was filled and the gap between the parallel plates was set to 1 mm. Next, the composition was pre-sheared at a shear stress of 1 Pa for 5 minutes, and then at a shear stress of 0.1 Pa for 10 minutes. Next, shear rheology measurements were performed at shear stresses ranging from 0.1 Pa to 1000 Pa, and the dilatancy coefficient was calculated from the measurement results of the viscosity at 10 Pa and 1000 Pa. Table 1 shows the results.

[0071] [Table 1]

[0072] The abbreviations for ionic liquids in Table 1 refer to the following ionic liquids. IL01: 1-Ethyl-3-methylimidazolium bis(trifluoromethanesulfonate)imide IL02: 1-Butyl-3-methylimidazolium bis(trifluoromethanesulfonate)imide IL31: 1-hydroxyethyl-3-methylimidazolium bis(trifluoromethanesulfonate)imide IL57: Diethylmethylammonium trifluoromethanesulfonate

[0073] From the results in Table 1, the resin particles are contained at 41.0 to 80.0 volume % and λ Cu It was found that the composition of Example 1, which contains an ionic liquid with a value in the range of 510 to 570 nm, has excellent dilatancy properties. On the other hand, the composition of Example 5, in which the content of the resin particles was less than 41.0% by volume, did not have dilatancy. Cu The composition of Example 4, which had a value of more than 570 nm, did not have dilatancy. [Industrial Applicability]

[0074] The composition has excellent stability and dilatancy, making it suitable for a wide range of applications, including as energy absorbing components in sports equipment, automotive parts, aerospace applications (e.g., airplanes, helicopters, space transportation, and military aerospace equipment), marine applications (boats, ships, and recreational vehicles), and trains. [Explanation of symbols]

[0075] 10: Materials 11: Shell layer 12: Composition layer 13: Outer shell layer 20: Protective equipment 21: Main body 22: Shoulder pads 23: Arm pad 24: Chest pad 25: Elbow pads 30: Gloves 31: Main body 32: Pad 40: Headgear 41: Main body 42: Pad

Claims

1. A composition comprising resin particles and an ionic liquid, The resin particles are The polymer swells in the ionic liquid and does not dissolve or diffuse monomolecularly; The average particle size is 1 to 20 μm, The content of the resin particles in the composition is 41.0 to 80.0% by volume, The ionic liquid is Contains at least one compound represented by the following structural formula: In the solution obtained by dissolving (acetylacetonate) (N,N,N',N'-tetramethylethylenediamine) copper (II) tetraphenylborate in the ionic liquid, Cu When the absorbance at the maximum absorption wavelength λ is set to 0.4, Cu is 510 to 570 nm, The content of the ionic liquid in the composition is 20.0 to 59.0 volume %. 【Chemistry 1】

2. 2. The composition according to claim 1, wherein the resin particles comprise at least one resin selected from the group consisting of a polyolefin resin, a polyurethane resin, a polyester resin, an epoxy resin, a melamine resin, a polystyrene resin, an acrylic resin, a polyamide resin, a polyether resin, and a silicone resin.

3. The composition of claim 1 or 2, wherein the resin particles comprise a crosslinked resin.

4. The composition according to any one of claims 1 to 3, wherein the resin particles are acrylic resin particles.

5. The composition according to claim 1, wherein the resin particles are at least one selected from the group consisting of crosslinked acrylic resin particles, crosslinked polyether resin particles, crosslinked polystyrene resin particles, and crosslinked silicone resin particles.

6. The composition of claim 5 , wherein the resin particles are crosslinked acrylic resin particles.

7. The composition of claim 6, wherein the resin particles are crosslinked methyl methacrylate.

8. The composition according to any one of claims 1 to 7, wherein the ionic liquid comprises at least one selected from the group consisting of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfone)imide, 1-butyl-3-methylimidazolium bis(trifluoromethanesulfone)imide, and 1-hydroxyethyl-3-methylimidazolium bis(trifluoromethanesulfone)imide.

9. The composition according to any one of claims 1 to 8, wherein the content of the ionic liquid in the composition is 30.0 to 59.0 volume %.

10. The composition according to any one of claims 1 to 9, having a dilatancy coefficient of 3.00 or more and 500.00 or less.

11. A member having two opposing shell layers and a composition layer comprising the composition according to any one of claims 1 to 10, disposed between the shell layers.

12. A protective device comprising the member according to claim 11.

Citation Information

Patent Citations

  • Acrylic resin composition

    JP1993093122A

  • Re-peelable aqueous dispersion-type acrylic self-adhesive composition and self-adhesive sheet

    JP2013100484A

  • Adhesive composition and adhesive sheet

    JP2017155243A

  • Dilatant composition

    JP2018080236A

  • Developing roller, developing device, and image formation device

    WO2012098590A1